Dicarbonyl-1κ2C-μ-chlorido-2:3κ2Cl:Cl-pentachlorido-2κ2Cl,3κ3Cl-[1(η6)-toluene]digallium(III)ruthenium(I)(Ru—Ga) - Danielle Smith; George N. Harakas (IUCrData, 2024)
The title compound, [RuGa2Cl6(C7H8)(CO)2] or [(CO)2(GaCl2)(η6-toluene)Ru]+[GaCl4]−, was isolated from the reaction of Ga2Cl4 with diphenylsilanediol in toluene, followed by the addition of Ru3(CO)12. The compound contains a ruthenium–gallium metal–metal bond with a length of 2.4575 (2) Å.